2004
DOI: 10.1042/bj20031664
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the human mitochondrial S-adenosylmethionine transporter: bacterial expression, reconstitution, functional characterization and tissue distribution

Abstract: The mitochondrial carriers are a family of transport proteins that, with a few exceptions, are found in the inner membranes of mitochondria. They shuttle metabolites and cofactors through this membrane, and connect cytoplasmic functions with others in the matrix. SAM (S-adenosylmethionine) has to be transported into the mitochondria where it is converted into S-adenosylhomocysteine in methylation reactions of DNA, RNA and proteins. The transport of SAM has been investigated in rat liver mitochondria, but no pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
138
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(138 citation statements)
references
References 52 publications
0
138
0
Order By: Relevance
“…The S-adenosylmethionine transporters are predicted to be strict exchangers, because the exchanged S-adenosylmethionine and S-adenosylhomocysteine are the substrate and product of methylation reactions. In agreement, the human version has no uniport activity (35), but the yeast version has some (36). Similarly, acylcarnitine/carnitine carriers are expected to be strict exchangers, because the exchanged substrates are the substrate and product of carnitine acyltransferase.…”
Section: Discussionmentioning
confidence: 78%
“…The S-adenosylmethionine transporters are predicted to be strict exchangers, because the exchanged S-adenosylmethionine and S-adenosylhomocysteine are the substrate and product of methylation reactions. In agreement, the human version has no uniport activity (35), but the yeast version has some (36). Similarly, acylcarnitine/carnitine carriers are expected to be strict exchangers, because the exchanged substrates are the substrate and product of carnitine acyltransferase.…”
Section: Discussionmentioning
confidence: 78%
“…Compartmentalization of SAM in isolated rat hepatocytes was first reported more than 2 decades ago [21], however, it was only recently demonstrated that rat liver mitochondria had a transport system for SAM whose activity can be inhibited by a close structural analog of SAM, such as SAH or sinefungin [24]. In a more recent study, Palmieri's group identified the human mitochondrial SAM transporter through over-expressing a human cDNA sequence of the mitochondrial SAM transporter in bacteria followed by purification and reconstitution of its product into phospholipid vesicles [23]. Their results showed that the SAM transporter gene was expressed in various human tissues including liver and was localized to the mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Since mitochondria have a relatively large pool of SAM [21], and the enzyme required for SAM synthesis (methionine adenosyltransferase, MAT) is present only in cytosol and not in the mitochondria [22], a specific SAM transporter is needed to maintain normal mitochondrial SAM levels. A human mitochondrial SAM transporter has been recently identified [23]. Moreover, it has been reported that increased cytosolic SAH caused a decrease in SAM concentration in the mitochondria in rat hepatocytes [24].…”
Section: Introductionmentioning
confidence: 99%
“…This pathway has been characterized at the molecular level in yeast (Marobbio et al, 2003) and human (Agrimi et al, 2004) mitochondria but has not yet been characterized in plants. Sequence comparison of SAMT1 with these nonplant mitochondrial SAMTs showed only moderate sequence similarity (see Supplemental Figure 1 online).…”
Section: Discussionmentioning
confidence: 99%
“…The first class includes structurally unrelated plasma membrane SAMTs from yeast (Rouillon et al, 1999) and the obligate intracellular bacterium Rickettsia prowazekii, the causative agent of epidemic typhus (Tucker et al, 2003). The second class contains mitochondrial SAMTs from yeast (Marobbio et al, 2003) and human mitochondria (Agrimi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%